2020
DOI: 10.1002/aoc.5619
|View full text |Cite
|
Sign up to set email alerts
|

Palladium nanoparticles stabilized by chitosan/PAAS nanofibers: A highly stable catalyst for Heck reaction

Abstract: Palladium chloride doped chitosan composite nanofibers were prepared by electrospinning with sodium polyacrylate (PAAS) as the co‐spinning agent. The composite nanofibers are subsequently treated at elevated temperature to improve their solvent resistance. The Pd (II) cations inside the composite nanofibers were reduced into uniform palladium nanoparticles (Pd NPs) with mean diameter of ~4.93 nm. These Pd NPs inside the chitosan composite nanofibers exhibited excellent catalytic activity for Heck reactions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Electrospinning is a unique method to fabricate continuous nanofibers with diameters ranging from tens of nanometers to several micrometers from polymer solution or melt and these novel nanofibers holds great potential applications in catalysis, filtration, and so on 20–22 . In our previous study, 23,24 we have demonstrated that these nanofibers are ideal supporting matrices to encapsulate catalytic metal nanoparticles as active and reusable heterogeneous catalysts. Due to the ultrathin fibers, the reactants can easily diffuse into the interior of fiber to reach transition metal active species inside the nanofibers and the products can back diffuse into reaction solution.…”
Section: Resultsmentioning
confidence: 99%
“…Electrospinning is a unique method to fabricate continuous nanofibers with diameters ranging from tens of nanometers to several micrometers from polymer solution or melt and these novel nanofibers holds great potential applications in catalysis, filtration, and so on 20–22 . In our previous study, 23,24 we have demonstrated that these nanofibers are ideal supporting matrices to encapsulate catalytic metal nanoparticles as active and reusable heterogeneous catalysts. Due to the ultrathin fibers, the reactants can easily diffuse into the interior of fiber to reach transition metal active species inside the nanofibers and the products can back diffuse into reaction solution.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 As a result, the chitosan solution was rapidly turned into fixed gel after addition of Pd 2+ cations. In our previous study, 32 we have successfully prepared the Pd 2+ /chitosan homogeneous solution by addition of trifluoroacetic acid. Then, with PAAS as the co-spinning agent, uniform palladium encapsulated chitosan composite nanofibers were prepared by electrospinning (Figure 1a).…”
Section: Characterization Of Palladium Nanoparticles Encapsulated Car...mentioning
confidence: 99%
“…As the phenyl groups inside the fibers were sulfonated by H 2 SO 4 , the free volume holes should have provided the place for the diffusion of reactants and reaction of crosslinking and sulfonation (Table 2). 30,31 Thus, the free volumes of polystyrene fiber mat and PS-SA-SO 3 H were analyzed by PALS, which was an efficient and sensitive technique to assess the size and concentration of free volumes. 32,33 As shown in Table 2, the crosslinking of polystyrene molecules inside the fibers would reduce the size and concentration of free volume holes.…”
Section: Characterization Of Polystyrene Ultrafine Fibersmentioning
confidence: 99%